A green way to simultaneously enhance the mechanical, flame retardant and anti-ultraviolet aging properties of polylactide composites by the incorporation of tannic acid derivatives. (February 2022) - Qiu, Shuang; Sun, Jun; Li, Hongfei; Gu, Xiaoyu; Fei, Bin; Zhang, Sheng
Highlights: The BA-TA-MEL was directly synthesized through a one-pot method without organic solvent. 5%BA-TA-MEL imparted a desirable UL-94 V-0 rating flame retardancy to PLA. The incorporation of BA-TA-MEL significantly improved the UV resistance capacity of PLA. BA-TA-MEL had a reinforcing effect on PLA and improved its mechanical properties. Abstract: Polylactic acid (PLA), characterized by its biodegradability, easy processing, and environmental friendliness, is regarded as one of the ideal substitutes for petroleum-based polymers. But, the flammability and UV light sensitivity of PLA often impact the safety and service life of its products. In this study, a bio-based additive (BA-TA-MEL) is synthesized via a one-pot method and used as a flame-retardant and anti-UV agent for PLA. The results show that PLA/5%BA-TA-MEL can achieve the desired V-0 degrade in the UL-94 test and an LOI value of 27.1%. Moreover, the PLA/5%BA-TA-MEL exhibits brilliant UV resistance, which increases the UPF to 290.4 from 0.4 of pure PLA. The BA-TA-MEL acts as a rigid particle in the matrix, effectively enhancing the tensile strength of materials. The current work develops a new approach to preparing biodegradable material with excellent performance and extended life to reduce the environmental pressure and pollution caused by petroleum-based plastics. Graphical abstract: Image, graphical abstract